Fortifikasi Tepung Eucheuma cottonii pada Nugget Udang Vaname sebagai Sumber Yodium: Fortification of Eucheuma cottonii Flour in Vaname Shrimp Nugget as a Source of Iodine - Djamaludin, Heder; Sulistiyati, Titik Dwi; Puspitasari, Yunita Eka; Notonegoro, Hartoyo (Amerta Nutrition, 2024)
Background: Humans require iodine as a micronutrient; a deficit in this mineral lowers IQ. Seaweed (E. cottonii) is a non-salt source of iodine. You can add E. cottonii flour to food items like nuggets. Aside from that, Vanname Shrimp are a high-protein fishery product that can be utilized as a base for nuggets. Therefore, to prevent iodine deficit, Vanname Shrimp nuggets supplemented with E. cottonii flour can be developed as a substitute food. Objectives: Fortification of E. cottonii flour in making Vanname Shrimp nuggets as an effort to increase the iodine content. Methods: Three replications of a non-factorial Completely Randomized Design (CRD) were used in the study. The fisheries products laboratory at Brawijaya University's Faculty of Fisheries and Marine Sciences (FPIK) was the site of the research. There were four additions of E. cottonii flour: 0%, 7.5%, 10%, and 12.5%. Iodine content is the parameter for chemical testing; elasticity is the parameter for physical testing; and color, scent, taste, and texture are the criteria for organoleptic testing (the hedonic approach for determining the optimal treatment utilizing the de Garmo and proximal testing). Results: The study found that adding different quantities of E. cottonii flour fortification significantly altered the iodine content and flexibility of Vanname Shrimp nuggets. E. cottonii flour is optimally fortified at a level of 7.5% treatment, with iodine content of 6.17 mcg/g, elasticity of 6.65 N, carbohydrate content of 77.04%, protein content of 7.78%, fat content of 3.67%, water content of 9.85%, and ash content of 1.66%. Conclusions: In order to prevent and treat iodine deficiency, the Vanname Shrimp nugget product fortified with E. cottonii flour should be further developed as a food option.